(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This paper investigates the connection between the decreasing density of trade unions and the mechanisms for resolving industrial disputes within India's manufacturing sector. By utilizing data from Labour Bureau reports (2015-2024), statistics from the Industrial Disputes Act, and recent labour reforms, this study evaluates how the 06resolution. The research uncovers a paradoxical trend: despite a decline in union membership from roughly 30% density in 1985 to 15% in 2024, industrial disputes saw a reduction of 73% between 2010 and 2021. This seemingly positive development conceals deeper issues such as heightened power imbalances, the diminishing of collective voice mechanisms, and an increasing dependence on individual grievance redressal. The study employs a quantitative analysis of official statistics alongside a qualitative review of legislative changes, particularly focusing on the Industrial Relations Code 2020. The findings suggest that the decline of unions has transitioned dispute resolution from collective negotiations to employer-dominated alternative dispute resolution (ADR) mechanisms, which raises concerns regarding worker agency and the sustainability of industrial harmony in the long run. This paper contributes to applied science by presenting empirical evidence of institutional changes in labour relations and offers policy recommendations aimed at establishing balanced dispute resolution frameworks in emerging economies.